2010
DOI: 10.1158/0008-5472.can-09-3777
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Conversion of SMAD7 Function from an Inhibitor into a Promoter of Cell Invasion

Abstract: Smad7 is an inhibitor of the transforming growth factor-β-activated signaling pathway. Under welloxygenated conditions, Smad7 is a potent inhibitor of carcinoma cell invasion. Paradoxically, however, the expression of Smad7 is upregulated across several cancers and may promote cancer progression. Hypoxia, which is frequently met in solid tumors, is an enhancer of carcinoma cell invasion and cancer progression. Here, we report that hypoxia activates the expression of Smad7 in a hypoxia-inducible factor-and von … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 48 publications
2
28
0
Order By: Relevance
“…25 Taken together, our data show that loss of PHD2 in the HSC compartment leads to enhanced HIF1a-related proliferation of early MPP fractions, which might be directly related to a reduced activity of the TGFb pathway.…”
Section: Loss Of Phd2 Enhances Proliferation Of Mpps Under Steady Stasupporting
confidence: 58%
See 1 more Smart Citation
“…25 Taken together, our data show that loss of PHD2 in the HSC compartment leads to enhanced HIF1a-related proliferation of early MPP fractions, which might be directly related to a reduced activity of the TGFb pathway.…”
Section: Loss Of Phd2 Enhances Proliferation Of Mpps Under Steady Stasupporting
confidence: 58%
“…19 Furthermore, SMAD7 can be regulated by hypoxia in a HIF1a/pVHL-dependent manner. 25 Accordingly, mice double deficient for PHD2 and HIF1a show no difference in SMAD7 or p21 expression compared with their WT littermates.…”
Section: Discussionmentioning
confidence: 98%
“…19 Furthermore, hypoxia seems to shape the TGF-b1 response by differentially affecting specific SMAD proteins, which execute the transcriptional TGF-b1 response. 20,21 Our data add to the understanding of the cooperative nature of hypoxia and TGF-b1 related pathways by demonstrating the effects of PHD2 on TGF-b1 processing.…”
mentioning
confidence: 67%
“…Previously it has been reported that SMAD7, which has an inhibitory function is increased in hypoxia, which might in addition at least in part explain the decrease in SMAD activity in the PHD2 knock down cells. 21 …”
Section: Phd2 Affects Active Tgf-b1 Protein Levelsmentioning
confidence: 99%
“…reported that hypoxic conditions could convert SMAD7 function from an inhibitor into a promoter of cell invasion in cancer, which was supported by evidence that increased SMAD7 expression in human cancer correlated with hypoxic gene expression. Further studies are needed to better understand how SMAD7 functions during EMT and metastasis 36.…”
Section: Discussionmentioning
confidence: 99%